The Representation of Hyponymy Relations in Explanatory Dictionaries: Theory and Practice - Tagaynazarova, Raxima Axmetovna (The Lingua Spectrum, 2026)
This article provides a comprehensive theoretical and practical analysis of the representation of hyponymic, or taxonomic, relations in explanatory dictionaries. Hyponymy is one of the most important types of lexical-semantic relations and plays a significant role in the hierarchical organization of word meanings, systematization of concepts, identification of semantic relationships between lexical units, and construction of dictionary definitions. The study examines major theoretical approaches to hyponymy in general linguistics, the relationship between the concepts of hyponym and hypernym, and relevant scholarly research conducted in Uzbek linguistics. The research material consists of 126 lexical units and their dictionary definitions selected from the two- and five-volume editions of the Explanatory Dictionary of the Uzbek Language. The selected material was analyzed using descriptive, comparative, grouping, and dictionary-definition analysis methods. The findings demonstrate that hyponymic relations are predominantly represented through the “genus proximum + differentia specifica” formula. At the same time, several inconsistencies were identified, including the absence of explicit hypernyms, disproportionate use of hypernyms at different levels of the semantic hierarchy, concealment of hyponymic relations through synonymous definitions, and ambiguous selection of polysemous hypernyms. These issues may reduce the semantic transparency, consistency, and systematic organization of dictionary entries. Based on the findings, the study proposes practical recommendations for improving lexicographic practice, standardizing dictionary definitions, and representing hyponymic relations through semantic networks and graphical models in electronic dictionaries.